2017
DOI: 10.23822/eurannaci.1764-1489.09
|View full text |Cite
|
Sign up to set email alerts
|

Serum estradiol concentration, estradiol-toprogesterone ratio and sputum IL-5 and IL-8 concentrations are increased in luteal phase of the menstrual cycle in perimenstrual asthma patients

Abstract: p = 0.039, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
6
0
4
Order By: Relevance
“…The association between deviations in levels of sex hormones and PMA has been suggested. Compared to non-PMA asthmatics, PMA subjects exhibit elevated estradiol levels in the luteal phase of the cycle (91). Rubio et al reported that on the 5th and 21st days of the menstrual cycle, approximately 80% of asthmatic women exhibit abnormal hormonal changes (92).…”
Section: Irregular Menstruationmentioning
confidence: 99%
“…The association between deviations in levels of sex hormones and PMA has been suggested. Compared to non-PMA asthmatics, PMA subjects exhibit elevated estradiol levels in the luteal phase of the cycle (91). Rubio et al reported that on the 5th and 21st days of the menstrual cycle, approximately 80% of asthmatic women exhibit abnormal hormonal changes (92).…”
Section: Irregular Menstruationmentioning
confidence: 99%
“…De acordo com diversos estudos clínicos e epidemiológicos, é visto que cerca de 30-40% das mulheres sofrem piora dos sintomas da asma no período perimenstrual (4) (26) , principalmente durante as fases de mudanças rápidas nas concentrações de estrogênio e progesterona 4 . Este fenômeno caracteriza o fenótipo da asma perimenstrual (PMA).…”
Section: Asma E O Ciclo Menstrualunclassified
“…Em um estudo comparativo prospectivo, no qual 33 mulheres com PMA foram avaliadas, notou-se que estas pacientes apresentaram níveis mais baixos de testosterona sérica ao longo do ciclo menstrual, quando comparadas com pacientes sem PMA 26 . É dado que a testosterona tem atividade imunossupressora e anti-inflamatória, o que diminui a resposta Th2 presente em quadros de asma 29 , e que níveis séricos elevados de testosterona livre estão associados a menores chances de asma em mulheres 12 .…”
Section: Asma E O Ciclo Menstrualunclassified
See 2 more Smart Citations